Correlations of chemical structure, atomic force microscopy (AFM) morphology, and reverse osmosis (RO) characteristics in aromatic polyester high-flux RO membranes - Kwak, SY; Yeom, MO; Roh, IJ; Kim, DY; Kim, JJ (ELSEVIER SCIENCE BV, 1997)
A homologous series of thin-film composite membranes was prepared by interfacial polymerization of various bisphenols possessing structural variations and trimesoyl chloride (TMC). Correlations between the inherent chemical nature of bisphenols with methyl or halogen substitutions on the biphenyl rings, reverse osmosis (RO) characteristics, and surface features characterized by atomic force microscopy (AFM) were studied. The methyl substitutions in bisphenol phenyl rings resulted in membranes with higher RO water flux but lower RO rejection, tending to give membrane surface morphology of irregular ambiguous nodule structure with reduced size and a smoother surface. The halogen substitutions were found to play an important role in enhancing the RO rejection of the resulting membranes; the rough surface appearance of uniform distinct nodule structure may also have contributed to obtaining higher rejections.